STRATEGI ADAPTASI BUDAYA MAHASISWA PROGRAM STUDI PGSD TEGAL UNNES DALAM MENGHADAPI PERBEDAAN KEBUDAYAAN - Tri Astuti (Universitas Muria Kudus, 2021)
The purpose of this study is to examine the cultural adaptation strategies of students in dealing with the differences in the city of Tegal and the obstacles they face in implementing cultural adaptation strategies.The research method used is a qualitative approach with the type of case study. The research was conducted at the Tegal PGSD campus and Kemandungan Village, Tegal City. The research subjects were PGSD Tegal FIP UNNES students. Data collection techniques used include observation, documentation and interviews. Interviews were conducted on students, Kemandungan residents and lecturers. Testing the validity of the data using triangulation techniques, namely source triangulation and technical triangulation. Data Analysis Techniques used in the Interactive Model Data Analysis include 1) Data Reduction 2) Presentation 3) Conclusion Drawing.The results of the study found that students carried out cultural adaptation strategies in the Tegal community by: 1) Understanding the way of life of the Tegal people, both through direct and indirect interactions, 2) Trying to accept cultural differences between them, 3) Damaging egocentrism and primordialism in themselves because in fact they are living in Tegal. The obstacles faced by PGSD UPP Tegal students in dealing with cultural differences in the City of Tegal are: a) Difficulty in translating the language and dialect used by the local community, b) Limited space for students at the village level, for example reluctance to join social organizations, c) Busy students on campus, For example, studying and joining campus organizations that are not related to the community.